PENGEMBANGAN PENGELOLAAN MATERIAL SEDIMEN PADA SPOILBANK WADUK SUTAMI - Tri Pambudi; Hari Nugroho; Suripin (Racic : Rab Construction Research, 2025)
The Sutami Dam is a multi-purpose dam currently managed by Perum Jasa Tirta 1. It is located in Karangkates Village, Malang Regency. Dredging activities in the Sutami Reservoir have led to new issues, particularly the sediment material resulting from the dredging process. The existing spoilbank capacity is still inadequate to meet the volume of material that needs to be dredged annually. Therefore, there is a need to develop the management of sediment material in the Sutami Reservoir’s spoilbank. This research is conducted to evaluate the sediment drying methods, assess the safety factor of embankment slope increases, and determine the volume increase in the spoilbank capacity. The data used in this study are sourced from soil parameter tests conducted by Perum Jasa Tirta 1, including grain size analysis and hydrometer analysis. The results of this study show that the most suitable dewatering method for sediment material management at Sutami Reservoir is Mechanical Dewatering (Filter Press). With the implementation of sediment management treatment, the embankment slope can be raised up to 9 meters at a 1:1 slope with a safety factor of 1.255. As a result, the potential increase in the spoilbank's holding capacity for one year is estimated to be between 2.016.500 – 2.303.800 m³ per year